Pemberdayaan Ekonomi Pesantren Berbasis Masyarakat - Agusti; Dassucik; Ahmad Hafas Rasyidi (CENDEKIA, 2022)
The purpose of this study is to describe the role of the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School in empowering the community's economy so that in the future an ideal system or construction of community economic empowerment can be realized that Islamic boarding schools can do. This research is included in qualitative research with a phenomenological approach, which is a form of research that aims to understand the real social reality as it is. Collecting data by interview, observation, documentation, and focus group discussion (FGD) and using interactive analysis. The results of this study indicate that the role of Islamic boarding schools in the economic empowerment of the surrounding community is very important in improving and improving the economic welfare of the surrounding community in the form of entrepreneurial motivation and management of business units, which exist in Islamic boarding schools, among others: trompa craftsmen, laundry services, shops, canteens, investment, convection, and trade. It does not only involve the students but also the community around the pesantren.